2011
DOI: 10.1016/j.brainres.2010.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of human neural precursor cell transplantation on endogenous neurogenesis after focal cerebral ischemia in the rat

Abstract: Little is known about the relationship between neuronal cell transplantation and endogenous neurogenesis after experimental stroke. We found previously that transplantation of neuronal precursors derived from BG01 human embryonic stem cells reduced infarct volume and improved behavioral outcome after distal middle cerebral artery occlusion (MCAO) in rats. In this study, transplantation was performed 14 d after distal MCAO and doublecortin (Dcx)-expressing cells in the subventricular zone (SVZ) and subgranular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(65 citation statements)
references
References 30 publications
1
64
0
Order By: Relevance
“…These results prompt further study of HIF, especially given HIF's role in inducing the expression of various previously discussed factors, including VEGF, EPO, and HB-EGF. Transplanted NPCs have also been shown to promote endogenous NPC proliferation in the SVZ [150,151] , angiogenesis [151] , and to release various trophic factors to promote axonal and dendritic plasticity [152] . The latter study found that the predominantly released factor was VEGF, which may explain the proliferative and angiogenic effects.…”
Section: Combinatorial Aproaches To Enhance Stroke Recoverymentioning
confidence: 99%
“…These results prompt further study of HIF, especially given HIF's role in inducing the expression of various previously discussed factors, including VEGF, EPO, and HB-EGF. Transplanted NPCs have also been shown to promote endogenous NPC proliferation in the SVZ [150,151] , angiogenesis [151] , and to release various trophic factors to promote axonal and dendritic plasticity [152] . The latter study found that the predominantly released factor was VEGF, which may explain the proliferative and angiogenic effects.…”
Section: Combinatorial Aproaches To Enhance Stroke Recoverymentioning
confidence: 99%
“…Inhibition or ablation of NSPCs in adult mice diminished poststroke motor and cognitive functional improvement [11,12,24], implying that endogenous neurogenesis directly participates in stroke recovery. The potential effects of post-stroke neurogenesis incude neuroprotection, immunomodulation, angiogenesis, neurotrophism, and possibly neuronal replacement [31].…”
Section: Discussionmentioning
confidence: 99%
“…11.020 0304-3940/© 2015 Elsevier Ireland Ltd. All rights reserved. ditional ablation of NSPCs in adult mice diminished poststroke motor and cognitive functional improvement and reduced synaptic connectivity [11,12,24], which demonstrated the importance of endogenous neurogenesis in stroke recovery. Therefore, enhancing endogenous neurogenesis may be a potential therapeutic strategy in stroke treatment.…”
Section: Introductionmentioning
confidence: 96%
“…Levels of NF expression increase 7 d after focal cerebral ischemia in the IBZ (25). A small number of studies have documented increased neural regeneration in the SVZ or IBZ with transplantation of non-neuronal cells in rodents after stroke (26). The present study, noted significantly increased levels of NF200 in the SVZ after cerebral I/R injury and in both the SVZ and striatum following HUMSC administration 14 d after surgery, so neural regeneration after ischemia was enhanced by intravenous HUMSC administration.…”
Section: Discussionmentioning
confidence: 99%